Modeling the impact of resilience factors and relational practice on performance of the supply chain - Mirela Cătălina Türkeș; Aurelia Felicia Stăncioiu; Roxana-Cristina Marinescu (Journal of Innovation & Knowledge (JIK), 2024)
Food businesses, especially those facing supply chain challenges, operate within a global environment characterized by uncertainty. The effects of the COVID-19 pandemic have underscored substantial losses in this sector. Our study aims to develop a mixed-formative-reflexive construct model that evaluates the impact of relational practices and resilience on the performance of enterprises within the Romanian food chain during crises. To select the sample, we employed a proportional stratified sampling method. The survey design included establishing the demographic profile of respondents, constructing items, and identifying latent variables specific to the proposed construct model. Data collection was conducted through an online questionnaire, resulting in 298 valid responses and a response rate of 35.06 %. Hypothesis testing and validation of the proposed construct model were performed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The research findings indicate that 56.9 % of the variance in food supply chain resilience can be attributed to the combined effects of proactive, reactive, and network design capabilities. The practical implications of the research suggest a need to reconsider planning strategies during crises. This involves reassessing risks, designing or redesigning products, and improving communication and collaboration with customers, suppliers, and other stakeholders. Therefore, enhancing relational practices and resilience can significantly and directly improve the performance of the food supply chain.
Keywords: C51; C52; C55; D30; M31; Q13; 650; Proactive capability; Reactive capability; Network design; Resilience; Relational practice; Supply chain performance